Exactitud y eficacia de impresiones digitales comparadas con impresiones convencionales en prótesis fija. - Vimos Pepinosa, Nicol Alexandra (2025)
Dental impressions are part of the elaboration of fixed dental prostheses; with this, it is possible to obtain the registration of soft and hard tissues of the oral cavity. There are currently two types of impressions, digital and conventional, each with benefits and drawbacks regarding accuracy and efficiency. This research aimed to establish digital dental impressions' accuracy, veracity, and precision compared to conventional impressions in fixed prostheses. To this end, the PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020) was used, through which the PICO question was posed: What is the level of accuracy and efficacy of digital impressions compared with conventional impressions in adult patients who need fixed prostheses? A total of 33 articles were included, where it was found that a digital impression's accuracy level is superior to a conventional one. Most of the authors also mentioned that the efficiency of digital impression systems is better than conventional ones in terms of time, cost, and patient comfort. Therefore, it was concluded that digital technologies have improved the accuracy and efficiency of dental impressions in fixed prostheses. However, more research is needed to improve the available scientific evidence.